A visita da Comissão Interamericana de Direitos Humanos na Argentina durante a ditadura civil-militar (1976-1983) | The Inter-American Commission on Human Rights’ on-site visit in Argentina during the civil-military dictatorship (1976-1983) - Dauer, Gabriel Roberto (Mural Internacional, 2021)
As violações de direitos humanos na ditadura civil-militar argentina (1976-1983) foram tema de foros multilaterais, sendo um deles a Comissão Interamericana de Direitos Humanos (CIDH) da Organização dos Estados Americanos. Nesse contexto, este trabalho analisa como a ditadura respondeu às críticas aos direitos humanos, particularmente quando da visita in loco da CIDH na Argentina em 1979 até a publicação de seu informe em 1980. Utilizamos da Análise de Política Externa para compreender as tomadas de decisão da ditadura para receber a CIDH, os atores envolvidos e as consequências nacionais e internacionais desse evento. A visita transformou o campo de oportunidades de denúncia e visibilidade de opositores ao expor as atrocidades da ditadura. Contudo, as decisões do regime não foram lineares: os militares não eram os únicos interessados em defender seus interesses; grupos de direitos humanos, exilados e organizações internacionais disputaram esse campo, somadas desavenças internas na Junta Militar que dificultaram uma congruência diplomática. Palavras-chave: Argentina; Ditadura; Comissão Interamericana de Direitos Humanos. ABSTRACT :Human rights violations during the argentine civil-military dictatorship (1976-1983) were a theme on multilateral forums, such as the Inter-American Commission on Human Rights (IACHR) of the Organization of American States (OAS). The article analyzes how the dictatorship reacted to criticisms regarding human rights violations in Argentina, especially during the IACHR’s on-site visit in Argentina in 1979 until the publication of its report in 1980. Theoretically, Foreign Policy Analysis concepts were articulated to understand the decision-making of the dictatorship to receive the IACHR, the actors involved, and the national and international consequences of the event. IACHR’s visit transformed the field of human rights actors’ opportunities of complaints and the visibility of opponents by exposing the atrocities of the dictatorship, whose decisions were not linear: the military was not the only interested actor in defending its interests; human rights groups, exiles, and international organizations also disputed this narrative, while internal disputes in the Military Junta made Argentina’s diplomatic congruence difficult. Keywords: Argentina; Dictatorship; Inter-American Commission on Human Rights. Recebido em: 31 mar. 2021 | Aceito em: 23 jun. 2021.